2020
DOI: 10.1111/trf.15738
|View full text |Cite
|
Sign up to set email alerts
|

Platelet depletion limits the severity but does not prevent the occurrence of experimental transfusion‐related acute lung injury

Abstract: BACKGROUND Transfusion‐related acute lung injury (TRALI) is a severe pulmonary reaction due to blood transfusions. The pathophysiology of this complication is still not widely elucidated by the scientific community, especially regarding the direct role of blood platelets within the cellular mechanism responsible for the development of TRALI. STUDY DESIGN AND METHODS In this study, a mouse model was used to induce the development of antibody‐mediated acute lung injury through injections of lipopolysaccharide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In the April issue of TRANSFUSION, Cognasse and colleagues also investigate the effect of PLT depletion using a 34‐1‐2S–mediated TRALI mouse model. At 30 minutes before TRALI induction with 34‐1‐2S, they treated mice with an anti‐GPIbα to deplete PLTs.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In the April issue of TRANSFUSION, Cognasse and colleagues also investigate the effect of PLT depletion using a 34‐1‐2S–mediated TRALI mouse model. At 30 minutes before TRALI induction with 34‐1‐2S, they treated mice with an anti‐GPIbα to deplete PLTs.…”
supporting
confidence: 83%
“…The discrepancies between the previously mentioned studies may be explained by the different experimental methods to deplete PLTs, by different duration of depletion methods, or by using different experimental read‐outs for lung injury, despite the fact that in all of these studies, the mice were infused with 34‐1‐2S to induce TRALI. Additionally, when investigating the involvement of PLTs in murine TRALI, Strait and colleagues did not treat the mice with low‐dose LPS before induction of TRALI, in contrast to the other studies . Perhaps superimposed on these discrepancies is the observation that the gut microbiome is a critical factor as to whether 34‐1‐2S–mediated TRALI can initiate .…”
mentioning
confidence: 99%
“…This is especially true for the clinically-relevant TRALI model based on injection of the anti-major histocompatibility complex (MHC) class I antibody, 34–1-2S [ 1 , 27 ]. Like in humans, this model features the 2 hits of TRALI pathophysiology with the first hit being represented by, for example, low levels of IL-10 (IL-10 KO mice or via depletion of CD4+ Tregs or DCs) [ 7 ], infusion of C-reactive protein (CRP) [ 28 ] or by priming with low-dose LPS [ 9 , [29] , [30] , [31] , [32] ]. The second hit is conveyed by the 34–1-2S antibody infusion.…”
Section: Recipient Platelet Involvement In Tralimentioning
confidence: 99%
“…Strikingly, several discrepancies have arisen regarding the role of recipient platelets in affecting TRALI responses by 34–1-2S [ 11 ]. Some studies have found recipient platelets to be pathogenic [ 29 , 37 ], while other studies found recipient platelets to be dispensable for the onset of TRALI [ 38 , 39 ] or not completely dispensable but with limited pathogenic involvement [ 30 , 31 ]. An early study by Looney et al found that in LPS-primed mice, in vivo platelet depletion using a rabbit anti-mouse platelet serum administered 2 hours before TRALI induction with 34–1-2 s protected against TRALI [ 29 ].…”
Section: Recipient Platelet Involvement In Tralimentioning
confidence: 99%
See 1 more Smart Citation